Analysis of the Digitalization of Accounting Information Systems in Supporting the Sustainability of MSMEs During the Pandemic (Study on MSMEs in Buleleng Regency) - I Putu Julianto; I Gd. Nandra Hary Wiguna; I Nyoman Putra Yasa (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2022)
This study discusses the Analysis of Digitalization of Accounting Information Systems in Supporting the Sustainability of MSMEs During a Pandemic (Study on MSMEs in Buleleng Regency). Accounting Information System is the most important part of any information management needs. Accounting information is directly related to financial documents and business activities. The problem raised is how to apply digitalization and the effectiveness of Accounting Information Systems in the MSME sector? The method used in this study is a qualitative research method. The results obtained are Digitization of information systems makes a fairly high contribution to MSMEs because of the ease with which they are obtained: 1. Speed ​​up the transaction process, 2. Efficiency in the use of labor, 3. Can be carried out direct supervision by the owner, 4. Ease of marketing, 5. Financial information is obtained in real time. Keywords: digitization; Accounting Information System; SMEs.